Health related lifestyles of adolescents : a study of smoking, alcohol and habit-forming drug use, and sexual activity, in a group of high-school students in Cape Town - Disler, Sally Ann (Department of Public Health and Family Medicine, 2017)
The AIM of the study from which the empirical data were obtained for this thesis, was the collection of basic demographic information and selected health related data from a group of adolescents at high-school in Cape Town. 1.2 The OBJECTIVES were Description of the demographic features of the pupils in Standards 8, 9 and 10 at a specific co-educational high school in Cape Town; Determination of the prevalence of smoking, and the attitudes to, and knowledge of the health risks of smoking; Determination of the prevalence of alcohol use, and the attitudes to, and knowledge of the health risks of consuming alcohol; Determination of the prevalence of habit-forming drug use, and the attitudes to, and knowledge of the health risks of using drugs; Determination of the sexual experience of the pupils, attitudes to and knowledge of the health risks of sexual activity, and knowledge of contraception and venereal disease; Examination of whether the above habits correlated within individuals i.e. whether those who smoked were more likely to use drugs or be sexually active, and vice versa.